Extraction and physical characterization of gelatin from knifefish (chitala ornata) skin as influenced by extraction time - Tecson, Jan Vincent DR.; Rumbaoa, Rowena Grace O. (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
ABSTRACT The global demand for gelatin has been increasing for years but a higher demand for alternative sources such as fish skin is being sought because of sociocultural reasons. Meanwhile, knifefish (Chitala ornata), an invasive fish species infesting Laguna lake in the Philippines, has limited food applications. The present study aimed to extract fish gelatin from the skin of knifefish, specifically, to determine the best extraction time for the process and to determine the physicochemical and gel characteristics of the extracted gelatin. It was found out that the optimum extraction time of 2 h produced a % yield of 13.48%. The proximate composition of the gelatin samples was 10.41% moisture, 86.09% crude protein, and 1.24% ash. The pH, L*, a* and b* color values were 5.67, 53.1, 0.11, and 14.79, respectively. The gel strength, viscosity, gelling temperature and melting temperature of the gelatin were 256.2 g, 6.9 cP, 17.3°C, and 33.7°C, respectively. It was found that knifefish is a potential commercial source of gelatin and the extracted fish gelatin was suitable for use in the food industry.
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Fish skin -- Philippines -- Processing; Gelatin